Effect of interfacial mass transfer on the dispersion in segmented flow in straight capillaries. Issue 12 (16th July 2015) - Deshpande, Jaydeep B.; Kulkarni, Amol A.
Abstract : The effect of interfacial mass transfer on the extent of dispersion in liquid‐liquid segmented flow in straight capillaries is studied. In the absence of interfacial mass transfer, dispersion coefficient was seen to go through a minimum with increasing flow rates. In the presence of mass transfer, physicochemical properties of both the phases and slug lengths were seen to vary along the capillary length. The extent of dispersion was always higher in the presence of interfacial mass transfer. The predictions using axial dispersion model deviated noticeably for larger capillaries as the model does not account for varying buoyancy, dynamic contacting, and Marangoni convection. Simulations of a first‐order interfacial reaction considering varying slug lengths showed a significant change in optimum operating parameters than the conventional approach. A special case of "drop‐on‐demand" type of controlled two‐phase flow in capillaries was also studied. © 2015 American Institute of Chemical Engineers AIChE J, 61: 4294–4308, 2015